EVALUASI PROGRAM KELOMPOK USAHA BERSAMA (KUBE) DALAM PEMBERDAYAAN PEREMPUAN RAWAN SOSIAL EKONOMI DI LINGKUNGAN LOPANG GEDE KOTA SERANG - Fahmi Fahmi; Anisa Anisa; Ika Nurhidayah; Sopi Nurhikmah; Rizka Azkal Azkiya; Rohani Pirdaus (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2021)
Research on evaluation of Joint Business Group programs (Kelompok Usaha Bersama/KUBE) in empowering socioeconomic vulnerable women (Perempuan Rawan Sosial Ekonomi/PRSE) conducted in Lopang sub-district, Serang sub-district, Serang city, Banten province. This study aims to evaluate the KUBE program in empowering socio-economic vulnerable women carried out by the Serang City Social Services. In this program evaluation research, the researcher uses a descriptive qualitative approach with the CIPP evaluation model (Context Evaluation, Input Evaluation, Process Evaluation and Product Evaluation). Furthermore, data collection techniques conducted by observation, structured interviews, and Focus Group Discussion (FGD). From the results of the research that researchers have done, the Joint Business Group program (KUBE) conducted by the Serang City Social Services has been running smoothly and has reached a level of success. With this program, many people feel helped so that they are able to manage the assistance. In addition, this program is also able to reduce the unemployment to increase local economy development.